Standard and emerging CMR methods for mitral regurgitation quantification - Fidock, Benjamin (Int J Cardiol, 2021)
BACKGROUND: There are several methods to quantify mitral regurgitation (MR) by cardiovascular magnetic resonance (CMR). The interoperability of these methods and their reproducibility remains undetermined. OBJECTIVE: To determine the agreement and reproducibility of different MR quantification methods by CMR across all aetiologies. METHODS: Thirty-five patients with MR were recruited (primary MR = 12, secondary MR = 10 and MVR = 13). Patients underwent CMR, including cines and four-dimensional flow (4D flow). Four methods were evaluated: MR(Standard) (left ventricular stroke volume - aortic forward flow by phase contrast), MR(LVRV) (left ventricular stroke volume - right ventricular stroke volume), MR(Jet) (direct jet quantification by 4D flow) and MR(MVAV) (mitral forward flow by 4D flow - aortic forward flow by 4D flow). For all cases and MR types, 520 MR volumes were recorded by these 4 methods for intra−/inter-observer tests. RESULTS: In primary MR, MR(MVAV) and MR(LVRV) were comparable to MR(Standard) (P > 0.05). MR(Jet) resulted in significantly higher MR volumes when compared to MR(Standard) (P < 0.05) In secondary MR and MVR cases, all methods were comparable. In intra-observer tests, MR(MVAV) demonstrated least bias with best limits of agreement (bias = −0.1 ml, −8 ml to 7.8 ml, P = 0.9) and best concordance correlation coefficient (CCC = 0.96, P < 0.01). In inter-observer tests, for primary MR and MVR, least bias and highest CCC were observed for MR(MVAV). For secondary MR, bias was lowest for MR(Jet) (−0.1 ml, P[bond, double bond]NS). CONCLUSION: CMR methods of MR quantification demonstrate agreement in secondary MR and MVR. In primary MR, this was not observed. Across all types of MR, MR(MVAV) quantification demonstrated the highest reproducibility and consistency.